Expression of gasdermin D in clear cell renal cell carcinoma and its effect on its biological function - Zhang, Jichi; Wang, Yujie; Ma, Jun; Aimudula, Ainiwaer (Frontiers in Oncology, 2023)
Background.Clear cell renal cell carcinoma (ccRCC) is the most common type of renal cell carcinoma, which suffers from the lack of diagnosis and treatment methods, and many patients cannot be diagnosed at the first time. Gasdermins D (GSDMD) is involved in inflammatory reaction and pyroptosis,and is considered as a potential therapeutic target. This paper aims to elucidate the diagnostic and prognostic value of GSDMD in ccRCC and its effect on the biological function of ccRCC. Method.TCGA database were used to compare the expression of GSDMD in tumor and normal tissues, analyze its correlation with cancer stage and overall survival time, and establish receiver operating characteristic (ROC) curve, which was confirmed by immunohistochemical staining of clinical samples and PCR and WB of cell lines. Differentially expressed genes (EDGs) and epithelial-mesenchymal transition (EMT) related genes of GSDMD were screened by TCGA database. Protein-protein interaction (PPI) of GSDMD was constructed by GeneMANIA and STRING, and GO and KEGG enrichment were analyzed by Metascape database. MTT, flow apoptosis and Transwell were used to detect the proliferation, apoptosis, invasion and migration of the transfected cells. Results.The expression of GSDMD in ccRCC was significantly correlated with the stage and overall survival of patients, and the tumor with high expression of GSDMD had worse stage and overall survival. GSDMD has some significance in the diagnosis of ccRCC (AUC=0.855). The results of EMT correlation analysis and enrichment analysis showed that GSDMD was correlated with genes and pathways related to proliferation and metastasis of ccRCC. The high expression of GSDMD in ccRCC by immunohistochemistry and cell experiments was confirmed. According to the prognostic information of clinical patients, it was found that GSDMD was significantly correlated with TNM stage, Fuhrman grade.etc , and the prognosis of patients with high expression of GSDMD was worse. After that, we confirmed that GSDMD is related to proliferation, invasion, migration and apoptosis of ccRCC by cell experiments. The low expression of GSDMD inhibits proliferation, invasion and migration of tumor and enhances apoptosis, and vice versa. Therefore, GSDMD can be used as a potential biological marker and therapeutic target for diagnosis and prognosis of ccRCC.